1976
DOI: 10.1038/bjc.1976.116
|View full text |Cite
|
Sign up to set email alerts
|

Monocytosis associated with the growth of transplanted syngeneic rat sarcomata differing in immunogenicity

Abstract: Summary.-The effect of the growth of two syngeneic transplanted sarcomata of widely differing biological properties on the number of monocytes in the blood of rats was measured (1) by binding of a specific antimacrophage serum to leucocytes, and (2) by sedimenting in a density gradient rosettes between mononuclear cells and antibody-coated sheep red cells under conditions in which B-cells are not brought down. For the 4 syngeneic sarcomata studied there was a progressive increase in the number of monocytes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Optimal bacterial phagocytosis by AM appears dependent upon humoral opsonic factors (Reynolds, Kazmierowski and Newball, 1975) and the maintenance of glucose metabolism for the provision of metabolic energy (Ouchi, Selvaraj and Sbarra, 1965 (Gee et al, 1974) and increased transport of glucose to provide an energy substrate (Bonventre and Mukkada, 1974;Gudewicz et al, 1976b Pike and Snyderman (1976) of depressed macrophage chemotactic behaviour under the influence of a lowmol.-wt heat-stable inhibitory factor isolated from growing tumours in mice, lend credence to this concept. The present findings of increased macrophage content of the alveolar space and altered macrophage physiological behaviour with tumour growth, must be considered with respect to the data of Eccles, Bandlow and Alexander (1976) and Eccles and Alexanider (1974). They observed increased macrophage content of growing tumours, which was related to the degree of immunogenicity of the tumour, and a parallel impairment of monocyte ability to enter a site of inflammation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Optimal bacterial phagocytosis by AM appears dependent upon humoral opsonic factors (Reynolds, Kazmierowski and Newball, 1975) and the maintenance of glucose metabolism for the provision of metabolic energy (Ouchi, Selvaraj and Sbarra, 1965 (Gee et al, 1974) and increased transport of glucose to provide an energy substrate (Bonventre and Mukkada, 1974;Gudewicz et al, 1976b Pike and Snyderman (1976) of depressed macrophage chemotactic behaviour under the influence of a lowmol.-wt heat-stable inhibitory factor isolated from growing tumours in mice, lend credence to this concept. The present findings of increased macrophage content of the alveolar space and altered macrophage physiological behaviour with tumour growth, must be considered with respect to the data of Eccles, Bandlow and Alexander (1976) and Eccles and Alexanider (1974). They observed increased macrophage content of growing tumours, which was related to the degree of immunogenicity of the tumour, and a parallel impairment of monocyte ability to enter a site of inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…They observed increased macrophage content of growing tumours, which was related to the degree of immunogenicity of the tumour, and a parallel impairment of monocyte ability to enter a site of inflammation. Tumour growth following transplantation, as investigated in rats with 2 svugenieic transplanted sarcomas, elicited a distinct monocytosis which declined after surgical removal of the tumour (Eccles et al, 1976). They proposed that states of "immunological anergy" with tumour growth may be related to the lack of availability and participation of macrophages in the inflammatory response, although the mechanism remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of this defect, qualitative or quantitative, was unclear. However, Eccles, Bandlow and Alexander (1976) argue that the defect is qualitative, since they have subsequently shown that such apparently anergic rats show a significant monocytosis rather than a monocytopenia. Furthermore, Normann and Sorkin (1976) have confirmed this observation in rats bearing DMBA-induced tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the irradiated mice were obviously unable to respond immunologically to either FS6 fibrosarcoma cells or SRBC until 2-3 weeks after irradiation, the changes in the macrophage content paralleled the expected rate of recovery of bone marrow and other haemopoietic tissues (Volkman and Collins, 1968). However, as recently demonstrated (Eccles, Bandlow and Alexander, 1976) there is an interrelationship between blood monocyte and tumour macrophage levels and the immunogenicity of the tumour, implying that the level of blood monocytes and tumour macrophages is under immunological control. The presence of T cells, albeit in low numbers, within the FS6 tumour mass, may be relevant to the mechanism determining the level of macrophages found associated with tumours, especially if it can be demonstrated that they show an affinity for the FS6 neo-39 plastic cells.…”
Section: Macrophage and Pmn Contentmentioning
confidence: 90%